Impact of transcranial direct current stimulation combined with median nerve stimulation on CRS-R in patients with prolonged disorders of consciousness after cerebral hemorrhage: protocol for a randomized controlled trial - Chen, Hanbo; Huang, Shujuan; Chen, Si; Wang, Zitian; Luo, Yong; Guo, Yongliang; Wen, Weifeng; Liang, Jinfeng; Deng, Yunhong; Lv, Xiao (Frontiers in Neurology, 2025)
BackgroundProlonged disorders of consciousness (pDoC) resulting from intracerebral hemorrhage (ICH) significantly impair patients’ quality of life. This study aims to investigate the therapeutic effects of transcranial direct current stimulation (tDCS) combined with median nerve stimulation (MNS) in patients with pDoC 3–12 months post-ICH.MethodsThis prospective, double-blind, randomized controlled trial will enroll 138 eligible patients with pDoC following ICH. Participants will be randomly assigned to three groups of 27 each: (1) tDCS + MNS, (2) sham tDCS + MNS, and (3) tDCS + sham MNS. The intervention will last for 4 weeks, followed by a 6-month follow-up period. The primary outcome measure is the change in the Coma Recovery Scale-Revised (CRS-R) scores. Secondary outcomes include electrophysiological and neuroimaging data. Assessments will be conducted at baseline, after 4 weeks of treatment, and at 2 weeks, 4 weeks, 12 weeks, and 24 weeks post-intervention.DiscussionThe strengths of this study include the combined intervention approach of tDCS and MNS, as well as comprehensive outcome measures. This intervention may promote consciousness recovery through multiple mechanisms, including enhanced neuroplasticity and modulation of brain networks. This study aims to provide a novel approach for consciousness-promoting treatment in pDoC, potentially improving patient prognosis and quality of life.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=203618, identifier ChiCTR2300075190.